Approach to Pediatric Patients during Surgical Interventions - Seher Ünver; Meltem Yıldırım (Güncel Pediatri)
A child’s surgical period usually contains unpleasant and difficult experiences, for the child and the parents. The child in this period experiences greater anxiety and distress. On the other hand, pediatric patients have complex states that directly effects their perioperative care during. Because their perioperative care includes not only the knowledge of general surgical procedure and care of a patient in the operating room. It also includes the specific understanding of a child’s airway, anatomy and physiology, the understanding of child development and care of the child and family. This review is prepared to present these differences of the pediatric surgical patients and the care during their perioperative period. (Journal of Current Pediatrics 2013; 11: 128-33)